ASSESSING THE MARKETING STRATEGIES OF AGRO-CHEMICAL COMPANIES AND THEIR IMPACT ON FARMER PURCHASE DECISIONS: A COMPREHENSIVE ANALYSIS OF AMRAVATI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
This research study analyses the marketing methods used by agro-chemical businesses in the Amravati District from 2011 to 2021 and determines how they affected farmers' purchasing choices. Insightful advice for industry stakeholders and legislators will be offered by the research, which seeks to shed light on the interplay between agro-chemical marketing techniques and farmer behaviour.This study examines several points of agro-chemical marketing tactics by using a mix of qualitative and quantitative research methodologies, such as interviews, surveys, and market analysis. In it, we look at how several agro-chemical firms in the Amravati District have positioned their products, used various distribution channels, set prices, and promoted their products over the last decade.